Contribution of Islamic Boarding Schools in Improving the Economy of Communities Around the Islamic Boarding School Environment - Fadli Muhtazam; M Shofi Anshori; Teguh Wijoyo; Intania Assai Nissa Sahiba (MONETARIUM: Journal of Economics Business and Management, 2024)
The increasing scope of Islamic boarding schools must be balanced with adequate facilities and infrastructure. So today's Islamic boarding schools must be able to maximize the economic potential of Islamic boarding schools. The source of human resource strength is not only from the Islamic boarding school community but also comes from the community around the Islamic boarding school. The research locations that have been determined by the researchers include the Islamic Boarding School which is part of the campus itself. This research uses a descriptive qualitative approach with data collection procedures using observation, interviews and documentation methods. The data collection technique itself involves data reduction, data description, and drawing conclusions. The research results show community employment opportunities in the Islamic boarding school environment which is a branch of the campus. The role of Islamic boarding schools, including opening employment opportunities, access to financing from cooperatives or micro banks, access to business capital and agricultural capital, assistance to MSMEs, meeting the needs of Islamic boarding schools from community businesses, community involvement in the Islamic boarding school school economy, and access to marketing of home industry products.